Elder abuse protocols: identifying key features and establishing evidence for their use and effectiveness. Issue 2 (14th March 2020) - Blundell, Barbara; Warren, Amy; Moir, Emily
ABSTRACT: Written protocols may guide staff responses to elder abuse. Their effectiveness is unclear, as protocols are generally unevaluated. This project aimed to review, evaluate, and update the Alliance for the Prevention of Elder Abuse: Western Australia's 2013 Protocol. A critical literature review identified key features of elder abuse protocols. Three focus groups (N = 19), and an online survey (N = 44) examined the usefulness and effectiveness of the 2013 Protocol and identified improvements. Seventy percent of survey respondents (n = 31) were familiar with the Protocol; all found it useful. Suggested updates included: example policies and resources; screening tools, signs, indicators, and guided risk assessment; further direction and training for front-line workers; and information about issues for diverse and vulnerable groups. An updated Protocol was developed and will be supported by stakeholder education. Ongoing maintenance is required in a changing service context, and future versions could be online and include features to support responses.